Chemical Origin of the Stability Difference between Copper(I)‐ and Silver(I)‐Based Halide Double Perovskites. (23rd August 2017) - Xiao, Zewen; Du, Ke‐Zhao; Meng, Weiwei; Mitzi, David B.; Yan, Yanfa
Abstract: Recently, Cu I ‐ and Ag I ‐based halide double perovskites have been proposed as promising candidates for overcoming the toxicity and instability issues inherent within the emerging Pb‐based halide perovskite absorbers. However, up to date, only Ag I ‐based halide double perovskites have been experimentally synthesized; there are no reports on successful synthesis of Cu I ‐based analogues. Here we show that, owing to the much higher energy level for the Cu 3d 10 orbitals than for the Ag 4d 10 orbitals, Cu I atoms energetically favor 4‐fold coordination, forming [CuX4 ] tetrahedra (X=halogen), but not 6‐fold coordination as required for [CuX6 ] octahedra. In contrast, Ag I atoms can have both 6‐ and 4‐fold coordinations. Our density functional theory calculations reveal that the synthesis of Cu I halide double perovskites may instead lead to non‐perovskites containing [CuX4 ] tetrahedra, as confirmed by our material synthesis efforts.